STRATEGI PENERJEMAHAN ISTILAH BUDAYA BALI PADA MEDIA PROMOSI PARIWISATA DI KABUPATEN BADUNG - Ni Luh Putu Krisnawati; Ni Ketut Alit Ida Setianingsih (LPPM Universitas Dhyana Pura, 2019)
ABSTRAKBali merupakan destinasi yang banyak dikunjungi oleh wisatawan lokal maupun mancanegara.Mereka datang ke Bali untuk melihat budaya Bali yang bergitu terkenal di mata dunia. Jikawisatawan yang berkunjung adalah wisatawan domestik maka Bahasa bukanlah menjadimasalah karena Bahasa ibu kita sama yaitu Bahasa Indonesia sehingga mereka dengan mudahdapat memahami budaya Bali. Akan tetapi jika yang datang berkunjung ke Bali adalahwisatawan mancanegara, maka Bahasa akan menjadi kendala, terutama kata-kata yangberhubungan dengan budaya. Penelitian ini merupakan penelitian deskriptif yang bertujuanuntuk meneliti terjemahan istilah budaya Bali ke Bahasa Inggris pada media promosipariwisata Wilayah Badung. Secara khusus penelitian ini akan mengidentifikasi istilah budayaBali apa saja yang digunakan pada media promosi pariwisata di wilayah Badung,mengklasifikasikan istilah budaya Bali tersebut ke dalam jenis-jenis cultural terms lalu untukmengetahui strategi penerjemahan yang digunakan untuk menerjemahkan istilah budaya Balitersebut dan jika istilah-istilah dalam budaya Bali yang sudah diterjemahkan maknanya masihkurang tepat maka akan diberikan makna yang benar yang bisa digunakan nantinya. Data yangdigunakan dalam penelitian ini diambil pada laman web Dinas Pariwisata Kabupaten Badungdan beberapa pamflet yang disediakan oleh jasa perjalanan wisata. Metode yang digunakanadalah metode dukumentasi dengan melakukan tehnik screenshoot pada laman web danpemotretan pada pamflet yang berisi istilah budaya Bali dan terjemahannya. Selanjutnya, datadiklasifikasi menurut jenis cultural terms lalu mengidentifikasi strategi terjemahan yangdigunakan untuk menerjemahkan istilah budaya Bali tersebut dan yang terakhir adalahmenyediakan makna yang sepadan untuk terjemahan istilah budaya Bali yang masih kurangsepadan. Teori yang digunakan pada penelitian ini adalah cultural terms oleh Newmark (1988)dan teori strategi penerjemahan oleh Molina dan Alber (2002). Dengan penelitian inidiharapkan bahwa terjemahan istilah budaya Bali tersebut sudah benar ke dalam Bahasa Inggrissehingga wisatawan manacanegara dapat memahami budaya Bali dengan baik dan benar.Kata Kunci: terjemahan, istilah budaya bali, strategi penerjemahan istilah budayaABSTRACTBali is a destination that is visited by many local and foreign tourists. They come to Bali to seeBalinese culture that is so famous in the eyes of the world. If tourists visiting are domestictourists, language is not a problem because our mother tongue is the same that is Indonesian,so they can easily understand Balinese culture. But if those who come to visit Bali are foreigntourists, then the language will become an obstacle, especially words related to culture. Thisresearch is a descriptive study that aims to examine the translation of Balinese cultural terms into English in the Badung region tourism promotion media. In particular, this study willidentify any Balinese cultural terms used in tourism promotion media in the Badung region,classify these Balinese cultural terms into types of cultural terms and then find out thetranslation strategies used to translate these Balinese cultural terms and if the meaning of theBalinese culture terms that has been translated is still inaccurate the correct meaning will begiven. The data used in this study was taken from the Badung Regency Tourism Office webpageand several pamphlets provided by tourist travel services. The method used is thedocumentation method by performing a screenshot technique on a webpage and shooting on apamphlet containing Balinese cultural terms and translations. Furthermore, the data isclassified according to cultural terms and then identifies the translation strategies used totranslate the terms of Balinese culture and the last is to provide matching meanings for thetranslation of Balinese cultural terms that are still not accurate. The theory used in this studyis cultural terms by Newmark (1988) and the theory of translation strategies by Molina andAlber (2002). With this research, it is expected that the translation of the Balinese cultural termis correct in English so that tourists from all over the world can understand Balinese cultureproperly and correctly.Keywords: translation, Balinese cultural term, strategy for translating cultural termsinto English in the Badung region tourism promotion media. In particular, this study willidentify any Balinese cultural terms used in tourism promotion media in the Badung region,classify these Balinese cultural terms into types of cultural terms and then find out thetranslation strategies used to translate these Balinese cultural terms and if the meaning of theBalinese culture terms that has been translated is still inaccurate the correct meaning will begiven. The data used in this study was taken from the Badung Regency Tourism Office webpageand several pamphlets provided by tourist travel services. The method used is thedocumentation method by performing a screenshot technique on a webpage and shooting on apamphlet containing Balinese cultural terms and translations. Furthermore, the data isclassified according to cultural terms and then identifies the translation strategies used totranslate the terms of Balinese culture and the last is to provide matching meanings for thetranslation of Balinese cultural terms that are still not accurate. The theory used in this studyis cultural terms by Newmark (1988) and the theory of translation strategies by Molina andAlber (2002). With this research, it is expected that the translation of the Balinese cultural termis correct in English so that tourists from all over the world can understand Balinese cultureproperly and correctly.Keywords: translation, Balinese cultural term, strategy for translating cultural terms